The impact of service quality and product quality towards customers satisfaction in Islamic banking: the moderating role of customer knowledge / Nur Athirah Yusoff and Mohammad Ismail - Yusoff, Nur Athirah; Ismail, Mohammad (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2020)
Over the last three decades, the emergence of a strong Islamic movement has created a renewed interest in Islamic economics. Gradually, Islamic banking started to fame, and the Islamic banking system has gained momentum globally and is not restricted only to Islamic banks. As banks offer similar products and services, competition becomes intensifying; thus, customers' satisfaction will determine their competitiveness and success. This study aims to propose a framework to investigate how customers create their satisfaction toward Islamic banking products and services, thus moderating customer knowledge. Based on the existing literature gaps, the researcher proposes a dependent variable (Customer Satisfaction), independent variables (Service Quality and Product Quality), and moderator (Customer Knowledge). In this study, four hypotheses are developed to determine the relationship between customer satisfaction, customer knowledge, and determinant factors. The study adopts purposive sampling and apply the quantitative method by distributing a survey questionnaire to the Islamic bank's customers. The Statistical Package for the Social Sciences (SPSS) and Partial Least Square (PLS) is used to analyse the data. All the results aims to target consumers' satisfaction in Islamic banking. Service quality (accessibility and serviceability), product quality (conformance and perceived quality) use as factors of customer satisfaction in Islamic banking. This study shows that Islamic banks should enhance their quality to increase their products' satisfaction. Besides, Islamic banks should emphasize their products and educate common people that their products comply with Shariah principles.